English Teaching-Learning Process At The Seventh Grade Of SMP N 2 Sawit Boyolali In 2013/2014 Academic Year - Mahayu, Beta Hima; , Drs. Djoko Srijono, M.Hum; , Dra. Dwi Haryanti, M. Hum (2014)
This study focuses on English teaching-learning process at the seventh grade of SMP N 2 Sawit Boyolali. This study is aimed at describing the teaching objective, syllabus, roles of teacher, roles of students, material, procedures, assignment, and problem faced by the teacher and the students in English teaching-learning process. This is a descriptive qualitative research. The subject of the study is the seventh grade of SMP N 2 Sawit Boyolali which consists of 26 students. The methods of collecting data are observation, interview, and documents analysis. In analyzing data, the writer uses an interactive model, namely the data reduction, the data display, and conclusion. Based on the research finding, the objective of teaching in SMP N 2 Sawit Boyolali are; the general instructional objective is based on curriculum that is to develop communicative competence in the four language skills and the specific instructional objective is to prepare the students implement the four basic skills, such as in listening, to understand what the speaker says, to produce both word sentence by using correct form and good pronunciation in speaking, to understand the contents of the text and enrich the vocabulary in reading, and to write word, sentence, and text by using correct form in writing. The curriculum is the 2006 Curriculum. The syllabus is theme-based syllabus. The teacher's roles are as a monitor, motivator, controller, model, material developer, and evaluator. The students' roles are as listener and performer. The material used in English teaching-learning process are textbook, workbook, picture, and cassette or CD. The classroom activities have almost focused on the four language skills. In SMP N 2 Sawit Boyolali, there are three stages of assessment, namely daily test, mid test, and final test. The writer also finds problems faced by the teacher are students discipline and they cannot put themselves in the right time and place and problem faced by the students is in writing a word or sentence.